2004
DOI: 10.1007/s10874-004-1214-y
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Dioxin and Furan Deposition in Relation to Land-Use and Other Pollutants: A Survey with Lichens

Abstract: Abstract. Polychlorodibenzeno-dioxins and polychlorodibenzeno-furans (PCDD/Fs) are considered among the most toxic compounds on earth. The aim of the present study was to evaluate atmospheric PCDD/F deposition and identify the areas with greater deposition of these compounds in an important industrialized and urbanized region of Portugal, using lichens as biomonitors. For this purpose, samples of the lichen Xanthoria parietina were collected at 60 sampling sites, covering urban, industrial, forestry and agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Considering that the process of incineration is growing in many countries (Leem et al 2003;Kuo et al 2008), and despite that in the last two decades a decline in dioxin levels was detected in some countries (Hays and Aylward 2003;Fierens et al 2003;Augusto et al 2004), this industrial activity is still a matter of public concern. In this regard, an important increase in morbidity and mortality in the city of Capivari de Baixo occurred in 2002, the mortality numbers were closely related to tumors, different from data of the whole country where tumors are the third cause of mortality (DATASUS 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the process of incineration is growing in many countries (Leem et al 2003;Kuo et al 2008), and despite that in the last two decades a decline in dioxin levels was detected in some countries (Hays and Aylward 2003;Fierens et al 2003;Augusto et al 2004), this industrial activity is still a matter of public concern. In this regard, an important increase in morbidity and mortality in the city of Capivari de Baixo occurred in 2002, the mortality numbers were closely related to tumors, different from data of the whole country where tumors are the third cause of mortality (DATASUS 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the soil, air and food near the incineration plants are contaminated with relatively high levels of dioxins and heavy metals, causing concern among the population living in such areas (Fierens et al 2003;Augusto et al 2004Augusto et al , 2007Masuda et al 2005;Huang et al 2006). In addition, exposure to the emission from solid waste incinerators seems to be the main cause of oxidative stress measured both in vivo and in vitro (Yoshida and Ogawa 2000;Leem et al 2003;Yoshida et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Thus a study of electroninduced reactions with furan is necessary to understand and model electron-driven processes in living cells. Furan is also an important molecule in nutrition industry [4][5][6] as well as environment sciences [7,8] as it is formed during thermal food processing and is a human carcinogen which is released into the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, X. parietina and R. canariensis could be used for monitoring PCDD/F concentrations. Using the lichen X. parietina as a biomonitor, Augusto et al (2004b) found that PCDD/F deposition occurred mainly in industrial and highly populated urban areas. The same authors found that the PCDD/F profiles detected in R. canariensis reflect air pollution rather than soil contamination (Augusto et al 2007b).…”
Section: Resultsmentioning
confidence: 99%